Chemostratigraphic correlation and Pb-Pb dating of carbonate sequences in the external Gariep belt and Kango inlier of the Saldania belt in Namibia and South Africa - Fölling, Peter Gerhard (Department of Geological Sciences, 2014)
Bibliography: leaves 238-251.